PENGARUH JUMLAH SUDU TERHADAP UNJUK KERJA PADA PROTOTYPE TURBIN ANGIN TIPE SAVONIUS - Joko Setiyono; Erlang Surya Budi Syahputra; Sulanjari Sulanjari; Agustina Dyah Setyowati; Ade Irawan (Ensiklopedia Research and Community Service Review, 2026)
The utilization of wind energy as a renewable source is continuously being developed to produce more efficient and environmentally friendly electricity. While most current turbines are horizontal-axis models, this research focuses on the design of Savonius-type Vertical Axis Wind Turbines (VAWT). Using models with 2, 3, and 4 blades constructed from 0.8 mm mild steel plates and a swept area of 80 cm × 80 cm. The wind speed used in this study is 4.3 m/s. The research results indicate that the 4-blade turbine produces the highest power output at 53.25 watts, with a turbine rotation speed of 195 rpmKeywords: Wind energy, wind turbine, Savonius vertical axis, electrical energy